2021
DOI: 10.1016/j.ajic.2021.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of COVID-19 outbreaks in 3 long-term care facilities in Graz, Austria

Abstract: Background: Nursing homes and long-term care facilities (LTCF) caring for elderly and chronically ill residents are at high risk to experience SARS-CoV-2 outbreaks. We report an outbreak of COVID-19 in three LTCFs of the Geriatric Health Centres of Graz, Austria lasting from 22nd March to 14th April, 2020. Aim: The objectives of our study were: (1) to elucidate contributing factors and transmission pathways of SARS-CoV-2, (2) to analyse symptoms of COVID-19 in the residents and health care workers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 8 publications
0
11
0
1
Order By: Relevance
“…In a LTC facility in West Virginia, the most helpful strategies managing outbreaks, and limiting virus spread and deaths, included early testing and isolation ( Shrader et al, 2021 ). In an Austrian study, it was concluded that delayed recognition of COVID-19-positive cases due to mild or non-specific symptoms contributed to virus transmission in multiple facilities, emphasizing the importance of low-threshold testing ( Zollner-Schwetz et al, 2021 ). Low-threshold testing of HCWs in a hospital early in the pandemic enabled the identification of asymptomatic and mildly symptomatic SARS-CoV-2-positive HCWs, when easily accessible public facilities were absent, preventing further spread of the infection ( Menting et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a LTC facility in West Virginia, the most helpful strategies managing outbreaks, and limiting virus spread and deaths, included early testing and isolation ( Shrader et al, 2021 ). In an Austrian study, it was concluded that delayed recognition of COVID-19-positive cases due to mild or non-specific symptoms contributed to virus transmission in multiple facilities, emphasizing the importance of low-threshold testing ( Zollner-Schwetz et al, 2021 ). Low-threshold testing of HCWs in a hospital early in the pandemic enabled the identification of asymptomatic and mildly symptomatic SARS-CoV-2-positive HCWs, when easily accessible public facilities were absent, preventing further spread of the infection ( Menting et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…SARS-CoV-2 is known to be transmitted by pre- and asymptomatic individuals, diagnosis and isolation of these cases are an essential part of outbreak control [ 7 ]. Furthermore, SARS-CoV-2 is known to present atypically in the elderly leading to potential delayed recognition and spread [ 8 ]. Noteworthy, five (63%) of the fully vaccinated cases were detected through one of these screenings.…”
Section: Discussionmentioning
confidence: 99%
“…Although it responds to very specific objectives, it should be noted that not all the elements involved in the care of the institutionalized older adult population during the COVID-19 period have been considered. As highlighted in other publications from the pandemic period, both nursing-home workers and family members have been involved in caring for older adults, as well as in the possible transmission of infection [ 15 , 17 , 21 , 26 , 83 , 120 , 121 ]. Workers have reported COVID-19 effects related to emotional health and workload due to staff shortages, as well as concerns about severe isolation measures, death of residents, and fear of transmitting the virus to family members [ 122 ].…”
Section: Concluding Remarks and Future Researchmentioning
confidence: 99%